One Pot Sequential Aldol condensation - Michael Addition – Sonogashira, and Heck Arylation toward Highly Functionalized Quinolines. (16th March 2023) - Ubba, Eethamukkala; Nawaz Khan, Fazlur-Rahman; Teja, Chitrala; Dalavai, Ramesh
Abstract: A facile Pd/Cu-cocatalyzed one-pot domino aldol condensation/Michael addition/Sonogashira coupling has been developed. The reaction of 2-chloro-3-formylquinolines (CFQs ), 1 acetophenones (APs ), 2 and terminal acetylenes, 3 by employing triethylamine as a base, solvent as well as a ligand under mild conditions gave highly functionalized 1, 5-diphenyl-3-(2-(2-phenylethynyl)quinolin-3- yl )pentane-1, 5-diones, 4a-j, Additionally accomplished Heck arylation using CFQs in the presence of Pd catalyst. The present methodology gave the desired synthetic building blocks in acceptable yields.